Hypothyroidism impairs development of the gastrointestinal tract in the ovine fetus - Young, Rhian; Lewandowska, Dominika; Long, Emily; Wooding, F. B. Peter; De Blasio, Miles J.; Davies, Katie L.; Camm, Emily J.; Sangild, Per T.; Fowden, Abigail L.; Forhead, Alison J. (Frontiers in Physiology, 2023)
Growth and maturation of the fetal gastrointestinal tract near term prepares the offspring for the onset of enteral nutrition at birth. Structural and functional changes are regulated by the prepartum rise in cortisol in the fetal circulation, although the role of the coincident rise in plasma tri-iodothyronine (T3) is unknown. This study examined the effect of hypothyroidism on the structural development of the gastrointestinal tract and the activity of brush-border digestive enzymes in the ovine fetus near term. In intact fetuses studied between 100 and 144 days of gestation (dGA; term ~ 145 days), plasma concentrations of T3, cortisol and gastrin; the mucosal thickness in the abomasum, duodenum, jejunum and ileum; and intestinal villus height and crypt depth increased with gestational age. Removal of the fetal thyroid gland at 105-110 dGA suppressed plasma thyroxine (T4) and T3 concentrations to the limit of assay detection in fetuses studied at 130 and 144 dGA, and decreased plasma cortisol and gastrin near term, compared to age-matched intact fetuses. Hypothyroidism was associated with reductions in the relative weights of the stomach compartments and small intestines, the outer perimeter of the intestines, the thickness of the gastric and intestinal mucosa, villus height and width, and crypt depth. The thickness of the mucosal epithelial cell layer and muscularis propria in the small intestines were not affected by gestational age or treatment. Activities of the brush border enzymes varied with gestational age in a manner that depended on the enzyme and region of the small intestines studied. In the ileum, maltase and dipeptidyl peptidase IV (DPPIV) activities were lower, and aminopeptidase N (ApN) were higher, in the hypothyroid compared to intact fetuses near term. These findings highlight the importance of thyroid hormones in the structural and functional development of the gastrointestinal tract near term, and indicate how hypothyroidism in utero may impair the transition to enteral nutrition and increase the risk of gastrointestinal disorders in the neonate.